2018
DOI: 10.1049/iet-cvi.2017.0382
|View full text |Cite
|
Sign up to set email alerts
|

Deep probabilistic human pose estimation

Abstract: The authors consider the problem of human pose estimation using probabilistic convolutional neural networks. They explore ways to improve human pose estimation accuracy on standard pose estimation benchmarks MPII human pose and Leeds Sports Pose (LSP) datasets using frameworks for probabilistic deep learning. Such frameworks transform deterministic neural network into a probabilistic one and allow sampling of independent and equiprobable hypotheses (different outputs) for a given input. Overlapping body parts … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 18 publications
(61 reference statements)
0
24
0
Order By: Relevance
“…Accuracy results are confirmed with the PCK ones in Table 2, where the scores are reported for each key joint separately and for the whole body. HPE algorithms can be useful for various tasks in many areas, such as action recognition, human detection, human attribute recognition, and various gait processing tasks [57]. We chose the HAR task as it represents many challenges due to occlusions and overlapping scenes.…”
Section: Results Of J-hmdb Datasetmentioning
confidence: 99%
“…Accuracy results are confirmed with the PCK ones in Table 2, where the scores are reported for each key joint separately and for the whole body. HPE algorithms can be useful for various tasks in many areas, such as action recognition, human detection, human attribute recognition, and various gait processing tasks [57]. We chose the HAR task as it represents many challenges due to occlusions and overlapping scenes.…”
Section: Results Of J-hmdb Datasetmentioning
confidence: 99%
“…If there is interference from moving objects in the field of view of the sports camera, the visual odometer will have a large estimation error or even fail. Aiming at the problem of moving objects in the scene interfering with the visual odometer, the random sampling consensus algorithm is currently the most mature and effective method [7]. is method fits the model and eliminates the data points that are inconsistent with the model as outliers.…”
Section: Related Workmentioning
confidence: 99%
“…The sparse coding model provides a more elegant calculation model for the formation mechanism of simple cell structures. Literature [ 4 ] uses the independent component analysis method to simulate the receptive field structure of simple cells. Studies have shown that the 2D receptive field profile of simple cells in the visual cortex is very similar to the core of the 2DGabor function.…”
Section: Related Workmentioning
confidence: 99%